The Effect of Assertive Behavior on Depression in Diabetes Mellitus Patients - Candra, I Wayan; Harini, I Gusti Ayu; Lestari, Agus Sri; Gama , I Ketut; Wijaya, Dewa Gede Sastra Ananta (Eduvest - Journal of Universal Studies, 2022)
The purpose of research is to know about the effect of assertive behavior to depression on diabetes mellitus patients. This study used pre-experimental design with ao ne-group pre-post test t design. The sample used is 1 7 people selected by purposive sampling technique. The results showed that the category of depression before being given assertive behavior treatment mostly in the moderate depression as many as 1 1 people (64.7%), and after being given assertive behavior showed that a decrease in the number of moderate depression to be 9 people ( 52.9 %). The results of this study were tested by paired-sample t-test statistic, the results obtained value (р) = 0.01 5 . The conclusion of research is assertive behavior can decrease the level of depression in patients with diabetes mellitus.